PENGARUH VARIASI JUMLAH TUMBUKAN TERHADAP NILAI MARSHALL HASIL PEMADATAN PADA ASPAL HRS-WC SECARA MANUAL DAN ELEKTRIK (Eternitas: Jurnal Teknik Sipil, 2023)
In this study, an analysis was conducted on the influence of the number of compaction impacts on the density of asphalt mixtures using the Marshall method on Hot Rolled Sheet Wearing Course (HRS-WC) Thin Asphalt Concrete (Lataston) mixture. The main objective of this research is to compare the compaction results between manual and electric methods. To achieve this, variations in the number of impacts were performed, namely 2 x 25, 2 x 40, 2 x 50, 2 x 60, and 2 x 75 impacts. The research results showed a significant difference between the manual and electric compaction methods in the observed Marshall parameters. Especially with 2 x 75 impacts, a noticeable difference was observed with a stability difference percentage of up to 2.505%. Therefore, it can be concluded that although the manual and electric compaction methods yield relatively similar results in terms of Void In Mix (VIM), Void In Material Aggregate (VMA), and Void Filled With Bitumen (VFB), there is a significant difference in stability, flow, and Marshall Quotient (MQ) parameters. This research has important implications in asphalt compaction practice and can be used as a guideline for selecting the most suitable compaction method to produce optimal quality asphalt mixtures.